Mawazo Institute 2020 COVID-19 Survey Report - The Mawazo Institute (My University, 2020)
This report draws on responses received from 501 individuals who were surveyed on the impact of the COVID-19 pandemic on their learning and ongoing research. The survey was carried out by the Mawazo Institute, a nonprofit research institute based in Nairobi, Kenya. The full findings are available at https://mawazoinstitute.org/our-publications.
Keywords: Africa; Early-career; E-learning; Higher Education; Mawazo Institute; Research; STEM; Survey; Women